Differential Synergistic Interactions Among Four Different Wheat-Infecting Viruses - Tatineni, Satyanarayana; Alexander, Jeff; Qu, Feng (Frontiers in Microbiology, 2022)
Field-grown wheat (Triticum aestivum L.) plants can be co-infected by multiple viruses, including wheat streak mosaic virus (WSMV), Triticum mosaic virus (TriMV), brome mosaic virus (BMV), and barley stripe mosaic virus (BSMV). These viruses belong to four different genera in three different families and are, hence, genetically divergent. However, the impact of potential co-infections with two, three, or all four of them on the viruses themselves, as well as the wheat host, has yet to be examined. This study examined bi-, tri-, and quadripartite interactions among these viruses in wheat for disease development and accumulation of viral genomic RNAs, in comparison with single virus infections. Co-infection of wheat by BMV and BSMV resulted in BMV-like symptoms with a drastic reduction in BSMV genomic RNA copies and coat protein accumulation, suggesting an antagonism-like effect exerted by BMV toward BSMV. However, co-infection of either BMV or BSMV with WSMV or TriMV led to more severe disease than singly infected wheat, but with a decrease or no significant change in the titers of interacting viruses in the presence of BMV or BSMV, respectively. These results were in stark contrast with exacerbated disease phenotype accompanied with enhanced virus titers caused by WSMV and TriMV co-infection. Co-infection of wheat by WSMV, TriMV, and BMV or BSMV resulted in enhanced synergistic disease accompanied with increased accumulation of TriMV and BMV but not WSMV or BSMV. Quadripartite interactions in co-infected wheat by all four viruses resulted in very severe disease synergism, leading to the death of most infected plants, but paradoxically, a drastic reduction in BSMV titer. Our results indicate that interactions among different viruses infecting the same plant host are more complex than previously thought, do not always entail increases in virus titers, and likely involve multiple mechanisms. These findings lay the foundation for additional mechanistic dissections of synergistic interactions among unrelated plant viruses.